Conceptual foundations of entrepreneurial strategy: Systematic literature review - Lidia Branco; Jo\~ao J. M. Ferreira; Shital Jayantilal (Entrepreneurial Business and Economics Review (EBER), 2021)
Objective: The objective of the article is to contribute to a greater and deeper understanding of the ES conceptualisation. The relevance of the topic of Entrepreneurial Strategy (ES) stems from growing interest of society in entrepreneurship, which has become extensively discussed although the concept of ES is still poorly understood. Research Design & Methods: A systematic literature review (SLR) referring to 427 articles from the Web of Science and Scopus databases was conducted. Findings: The results made it possible to identify five ES conceptual foundations: i) economic theory and entrepreneurship; ii) entrepreneurial strategies, concept - theory; iii) entrepreneurial strategies, framework - models; iv) entrepreneurial strategies, contexts - application; and v) entrepreneurial strategies, application - metrics. Implications & Recommendations: This SLR can help to highlight the gap in theories on ES, its conceptualisation and the fundamentals found in the literature. A research agenda is suggested for each ES foundation identified. Contribution & Value Added: The study is innovative given there have been no other identified SLR studies on the ES concept. The study attempts to contribute towards the literature by offering a model of interactions of the ES foundations.
Keywords: L26; M01; M21; 330; entrepreneurial strategy; conceptualisation; entrepreneurship; strategy; systematic literature review